(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2015)
This study provides a stocktaking of progress and shortcomings inIndia’s march towards universalization of elementary education (UEE), whilstaddressing concerns of equity, inclusion, and quality from the central focuswhich looks into the dimensions of locational disadvantage, social exclusion,gender disparity, and special needs for children of other neglected groups. Itfocuses on gaps in enrolment, infrastructural provisioning, equity concerns interms of being inclusive in the context of schools functioning, teachers(social group, training, motivation, transaction and so on), management, andgovernance issues. The extent and manifestations of non-inclusion or exclusionin the educational context is also related to the capacity of the State asreflected in the policy fuzziness and ambiguities.